Characterization of Pseudomonas aeruginosa bacteriophages and control hemorrhagic pneumonia on a mice model - Zhang, Yanjie; Wang, Ruiqing; Hu, Qingxia; Lv, Ni; Zhang, Likun; Yang, Zengqi; Zhou, Yefei; Wang, Xinglong (Frontiers in Microbiology, 2024)
Pseudomonas aeruginosa is one of the most common pathogens causing hemorrhagic pneumonia in Chinese forest musk deer. Multidrug-resistant P. aeruginosa is frequently isolated from the lungs of affected musk deer in Shaanxi Province, China. With the increasing bacterial drug resistance, commonly used antibiotics have shown limited efficacy against drug-resistant P. aeruginosa. Therefore, phages have garnered attention as a promising alternative to antibiotics among researchers.In this study, phages vB_PaeP_YL1 and vB_PaeP_YL2 (respectively referred to as YL1 and YL2) were isolated from mixed sewage samples from a farm. YL1 and YL2 exhibit an icosahedral head and a non-contractile short tail, belonging to the Podoviridae family. Identification results demonstrate good tolerance to low temperatures and pH levels, with minimal variation in potency within 30 minutes of UV irradiation. The MOI for both YL1 and YL2 was 0.1, and their one-step growth curve latent periods were 10 minutes and 20 minutes, respectively. Moreover, both single phage and phage cocktail effectively inhibited the growth of the host bacteria in vitro, with the phage cocktail showing superior inhibitory effects compared to the single phage. YL1 and YL2 possess double-stranded DNA genomes, with YL1 having a genome size of 72,187bp and a total G+C content of 55.02%, while YL2 has a genome size of 72,060bp and a total G+C content of 54.98%. YL1 and YL2 are predicted to have 93 and 92 open reading frames (ORFs), respectively, and no ORFs related to drug resistance or lysogeny were found in both phages. Genome annotation and phylogenetic analysis revealed that YL1 is closely related to vB_PaeP_FBPa1 (ON857943), while YL2 is closely related to vB_PaeP_FBPa1 (ON857943) and Phage26 (NC041907). In a mouse model of hemorrhagic pneumonia, phage cocktail treatment showed better control of the disease and significantly reduced lung bacterial load compared to single phage treatment. Therefore, YL1 and YL2 have the potential for the prevention and treatment of multidrug-resistant P. aeruginosa infections.